2015
DOI: 10.3892/mco.2015.643
|View full text |Cite
|
Sign up to set email alerts
|

Role of CXC chemokine receptor type 7 in carcinogenesis and lymph node metastasis of colon cancer

Abstract: Abstract. Upregulated expression of the CXC chemokine receptor type 7 (CXCR7) promotes breast, lung and prostate cancer progression and metastasis. However, the role of CXCR7 in colon cancer has not been determined. We hypothesized that increased CXCR7 expression may contribute to human colon cancer occurrence and progression. Reverse transcription quantitative polymerase chain reaction and western blot analysis were performed on 34 malignant and 18 normal colon tissue specimens. The specimens were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It is well known that CXCR4 and its ligand CXCL12 play a significant role in tumorigenesis and metastasis of various tumors 4 . Similarly, high expression of CXCR7 has been confirmed in various types of tumors as well and is involved in tumorigenesis, metastasis, and drug resistance 5 - 7 . CXCR7 has been identified as a novel receptor for CXCL12 with higher affinity of binding CXCL12 than CXCR4 in recent years 8 .…”
Section: Introductionmentioning
confidence: 95%
“…It is well known that CXCR4 and its ligand CXCL12 play a significant role in tumorigenesis and metastasis of various tumors 4 . Similarly, high expression of CXCR7 has been confirmed in various types of tumors as well and is involved in tumorigenesis, metastasis, and drug resistance 5 - 7 . CXCR7 has been identified as a novel receptor for CXCL12 with higher affinity of binding CXCL12 than CXCR4 in recent years 8 .…”
Section: Introductionmentioning
confidence: 95%
“…6 It has been reported that CXCR7 is highly expressed in colon cancer. 7 More recently, numerous studies confirmed that CXCR7 is also expressed in other types of cancer (eg, pancreatic, thyroid, prostate, breast, esophageal, hepatocellular carcinoma, bladder), promoting tumor growth and metastasis. [8][9][10][11][12][13][14] Neovascularization is an essential step for tumor growth, invasion, and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Chemokine receptor 7 (CXCR7)—formerly known as RDC1—is the second receptor for C‐X‐C motif chemokine 12 (CXCL12)/stromal cell‐derived factor 1 (SDF‐1), with a 10‐fold higher binding capacity than CXCR4 . It has been reported that CXCR7 is highly expressed in colon cancer . More recently, numerous studies confirmed that CXCR7 is also expressed in other types of cancer (eg, pancreatic, thyroid, prostate, breast, esophageal, hepatocellular carcinoma, bladder), promoting tumor growth and metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…The expression level of CXCR7 in lung tissues is twelve times higher than in liver tissue [ 93 , 103 ]. Increased expression of CXCR7 was also reported in CRC with lymph node metastasis and considered a good predictor of lymph node metastasis in CRC patients [ 104 ]. The systemic treatment with CXCR7 antagonists reduces tumor expansion in lungs of experimental mice inoculated with HT-29 or C26 cancer cells [ 103 ].…”
Section: Signaling In Crc Growth Invasion and Metastasismentioning
confidence: 99%